Implementasi Metode ROC dan SMART dalam Sistem Pendukung Keputusan Pemilihan Lokasi Cabang Bimbingan Belajar AlphaKids Generation - Imran Lubis (CV. Hawari, 2025)
Strategic location selection is a crucial factor in the success of business expansion, including in the education sector such as tutoring institutions. AlphaKids Generation, as a growing tutoring center, requires an objective and structured system to determine new branch locations. This study aims to design a decision support system based on the Rank Order Centroid (ROC) and Simple Multi Attribute Rating Technique (SMART) methods to assist the location selection process. The ROC method is used to determine the weight of criteria based on their priority, while the SMART method evaluates location alternatives based on performance scores and assigned weights. The system was developed using the Rapid Application Development (RAD) approach and implemented on a web-based platform. The results show that location A5 (Jl. Karya Jaya) is the best alternative, achieving the highest score of 1.000. This system supports decision-makers in selecting the most appropriate location through a quantitative and objective analysis.